2016
DOI: 10.3233/jad-150751
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration

Abstract: Background Meta-analysis studies showed that smokers have increased risk for developing Alzheimer’s disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. Objective The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. Methods Adult male A/J mice were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 96 publications
2
32
0
Order By: Relevance
“…The effects of CS worsened with duration of exposure, but were partly reversed by short-term withdrawal. Furthermore, the abnormalities correspond with recent findings of CS-associated impairments in insulin and IGF signaling and altered expression of myelin-associated genes in frontal lobes of the CS-exposed mice [36, 37]. The use of MALDI-IMS to detect biochemical indices of WM degeneration holds promise for future investigations, including studies of human brains with AD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The effects of CS worsened with duration of exposure, but were partly reversed by short-term withdrawal. Furthermore, the abnormalities correspond with recent findings of CS-associated impairments in insulin and IGF signaling and altered expression of myelin-associated genes in frontal lobes of the CS-exposed mice [36, 37]. The use of MALDI-IMS to detect biochemical indices of WM degeneration holds promise for future investigations, including studies of human brains with AD.…”
Section: Discussionsupporting
confidence: 82%
“…Although the vast majority of research on nitrosamine-induced diseases pertains to carcinogenesis, emerging evidence supports the concept that low-level nitrosamine exposures also threaten health by causing progressive degenerative diseases linked to tissue injury, inflammation, impairments in insulin/IGF signaling through cell survival and metabolic pathways, oxidative and nitrosative stress, and dysregulated lipid metabolism [42–44]. In this regard, we have shown that NNK and other nitrosamines cause neurodegeneration [31, 44] including in WM [4547] with abnormalities similar to those described herein and in recent CS exposure related publications [36, 37]. …”
Section: Discussionsupporting
confidence: 67%
“…M. de la Monte, 2012; S. M. de la Monte, Re, Longato, & Tong, 2012; Yu et al, 2016), including ARBD (S. de la Monte et al, 2012; S.…”
Section: Discussionmentioning
confidence: 99%
“…77 Yet, mouse models of cigarette smoke exposure in adulthood suggest that it broadly reduces myelin synthesis and maintenance that could not be reversed by short-term withdrawal. 78 These largely mixed results on the direction of the link between smoking and white matter architecture suggest a more complex relationship compared to obesity or cardiorespiratory fitness; however, the emerging findings do make it clear that smoking does have a strong association with the integrity of the underlying white matter systems.…”
Section: Associations Between Peripheral Health and White Mattermentioning
confidence: 99%